Long-Term Macular Changes in the First Proband of Autosomal Dominant Vitreoretinochoroidopathy (ADVIRC) Due to a Newly Identified Mutation in BEST1. (2nd January 2016) - Chen, Connie J.; Kaufman, Stuart; Packo, Kirk; Stöhr, Heidi; Weber, Bernhard H. F.; Goldberg, Morton F.
Abstract: Background : Mutations in BEST1 account for autosomal dominant vitreoretinochoroidopathy (ADVIRC), a rare inherited retinal dystrophy with presenile cataracts and incomplete anterior segment development. The long-term clinical findings and visual prognosis of these patients continues to evolve over time. Materials and Methods : The retina was assessed by fundus photography, fluorescein angiography, and spectral domain optical coherence tomography. Sanger dideoxy chain-termination sequencing identified mutations in BEST1 . Bioinformatic tools were used to predict changes in splicing. An in vitro splicing assay was applied to evaluate for altered pre-mRNA splicing. Results : Long-term follow up of the first ever reported ADVIRC proband revealed progressive foveal atrophy in both eyes 3 decades after his initial presentation. Progressive retinal ischemia, bilateral iris atrophy, and pseudophakodnesis were observed on follow up. The patient was heterozygous for a c.248G > A missense mutation in exon 4 of BEST1, affecting a highly conserved transmembrane domain. Although computational prediction models suggest a change in the binding probability of splicing-associated SR proteins, in vitro splicing assays failed to demonstrate an effect of the c.248G > A mutation on splicing of BEST1 exon 3 or exon 4. Conclusions : Progressive posterior chorioretinal changes occurred over time in the initial ADVIRC proband, leading to visual loss. The causative mutation in this patient falls in the transmembrane domain of the BEST1 protein, with unclear functional consequences. Although previous studies showed alteration in pre-mRNA splicing, in vitro splicing assays failed to demonstrate this in our patient.